(3GdhLjR aj EOGQI GdCYeGd GdOhdjI s - (3SejQ(B, (3Hf YHO GdYRjRs ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jJfGhd GdcJGH GdCYeGd GdOhdjI eaghegG, WHjYJgG heLGdGJgG hjVe GdJLGQI GdOhdjI, GdYhdeI, GdefXeI GdYGdejI ddJLGQI hGdJcGed GdGbJUGOj HGdEVGaI Edi GdJLGQI GdOhdjI, ejRGf GdeOahYGJ hCSYGQ UQa GdYedGJ, hjJMOK cPdc Yf GdESJKeGQ GdCLfHj, CfhGYg, fXQjGJg heNGWQg HeG ajg HjFI GdCYeGd GdOhdjI hJMdjd eNGWQgG, GdHjFI GdeGdjI GdOhdjI, haj GdCNjQ JMOK Yf GdJNWjW GdGSJQGJjLj hGdEOGQI GdGSJQGJjLjI aj GdTQcGJ eJYOOI GdLfSjGJ(B. s
(3HjHdjhZQGajG(B: (3U U(B.190-194s
Keywords: (3EOGQI GdCYeGds; (3GdESJKeGQGJ GdCLfHjIs; (3GdJLGQI GdNGQLjIs